Heuristictool, tool for supporting heuristic assessments to interactive systems through ontologies (2021)
This work presents a tool called HeuristicTool, by means of which the heuristic evaluation process is supported, allowing evaluators to improve the process of analyzing the results and, in general, the development of said evaluations. During its development and permanent updating, ontologies were included to facilitate the capitalization and transfer of knowledge between the different evaluators. The above through KACTUS, a methodology that proposes steps in relation to: the specification of the application, preliminary design based on ontological categories and a refinement and structuring of the ontology. A group of three experts rated 6 ontology variables, consolidating an average of 4.7 out of 5. In addition, an evaluation of the platform's usability presented satisfactory results, using Jakob Nielsen's battery of heuristics. The main result was an application that gives users the possibility of reviewing structured evaluations in a knowledge base, in order to improve decision making.